A Numerical Model for Analysis of Heat Transfer in MHD Casson Fluid with Radiation and Viscous Dissipation - Shankar, Gollapalli; Sheri, Siva Reddy (International Journal of Integrated Engineering, 2023)
This article is, concerned a numerical model for analysis of heat transfer (HT) in MHD Casson fluid (CF) with radiation and viscous dissipation. The governing PDE’s are developed for the physical model and converted into non-dimensional form and then with the help of Galerkin finite element method (GFEM) solution is obtained. The impact of dimensionless parameters which are supervising the flow such as Magnetic parameter , Casson parameter ( ) thermal Grashof number Permeability of porous medium Prandtl number Heat absorption parameter Viscous dissipation and Radiation parameter are analyzed through graphs for fluid properties. The results obtained were compared with earlier reported results for correctness